Cardio‐hepatic risk assessment by CMR imaging in liver transplant candidates. Issue 5 (11th April 2018) - Reddy, Sahadev T.; Thai, Ngoc L.; Oliva, Jose; Tom, Kusum B.; Dishart, Michael K.; Doyle, Mark; Yamrozik, June A.; Williams, Ronald B.; Shah, Moneal; Wani, Adil; Singh, Anil; Maheswary, Rishi; et al.
Abstract: Background: The preoperative workup of orthotopic liver transplantation (OLT) patients is practically complex given the need for multiple imaging modalities. We recently demonstrated in our proof‐of‐concept study the value of a one‐stop‐shop approach using cardiovascular MRI (CMR) to address this complex problem. However, this approach requires further validation in a larger cohort, as detection of hepatocellular carcinoma (HCC) as well as cardiovascular risk assessment is critically important in these patients. We hypothesized that coronary risk assessment and HCC detectability is acceptable using the one‐stop‐shop CMR approach. Methods: In this observational study, patients underwent CMRI evaluation including cardiac function, stress CMR, thoracoabdominal MRA, and abdominal MRI on a standard MRI scanner in one examination. Results: Over 8 years, 252 OLT candidates underwent evaluation in the cardiac MRI suit. The completion rates for each segment of the CMR examination were 99% for function, 95% completed stress CMR, 93% completed LGE for viability, 85% for liver MRI, and 87% for MRA. A negative CMR stress examination had 100% CAD event‐free survival at 12 months. A total of 63 (29%) patients proceeded to OLT. Explant pathology confirmed detection/exclusion of HCC. Conclusions: This study further defines the population suitable for the one‐stop‐shop CMR concept for preop evaluation of OLT candidates providing a road map for integrated testing in this complex patient population for evaluation of cardiac risk and detection of HCC lesions.